Penerapan E-Government dalam Reformasi Sistem Pelayanan Publik: Studi Kasus di Universitas Negeri Padang - Azfirmawarman, Dony; Syamsir, Syamsir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The implementation of E-government in facing the era of industrial revolution 4.0 affects various aspects of life in Indonesia, especially in the government sector. The reform of implementing E-government in Indonesia is very interesting to research considering that Indonesia, especially Padang State University (UNP), is also required to implement public service reforms based on the industrial revolution 4.0 among the campus academic community to support World Class Bureaucracy. Therefore, this article aims to describe the implementation of E-Government in relation to public service reform at Padang State University. The research method used in this research is descriptive qualitative with data collection techniques through literature review. The data analysis used in this research includes data collection, data presentation, data reduction, and drawing conclusions. The results of the research show that the implementation of E-government in public service reform at Padang State University has experienced good progress and improvement both in terms of facilities and infrastructure with the help of information technology to face the era of revolution 4.0. Apart from that, there are also obstacles in implementing E-Government at UNP, including facilities, human resources, budget funds, legal entities, and the transition of work systems and human resource functions.